UNDERSTANDING STUDENT PERSPECTIVES ON LIBRARY SERVICES: UNIVERSITY OF CALABAR CASE STUDY - Okon, Emeka Obi; Ibe , Chinyere Nwosu (Current Journal of Library and Information Sciences (CJLIS), 2023)
The modern university serves as a cornerstone for the advancement of knowledge that caters to the practical needs of individuals, society, and diverse professions. It remains a pivotal institution globally, thriving on its two fundamental services: fulfilling humanity’s unquenchable thirst for knowledge and meeting society’s collective hunger for wisdom. This study delves into the evolving landscape of university education, particularly the shifting dynamics of student learning after secondary school, and the pivotal role that expansive faculties, robust enrollments, and substantial resources play in the pursuit of multifaceted knowledge domains. In an ever-changing educational landscape, universities continue to be instrumental in shaping the intellectual growth of individuals and the progress of societies.